Mechanical and Enzyme Assisted Fractionation Process for a Sustainable Production of Black Soldier Fly (Hermetia illucens) Ingredients - Azzollini, Domenico; van Iwaarden, Amber; Lakemond, Catriona M. M.; Fogliano, Vincenzo (Frontiers in Sustainable Food Systems, 2020)
This study aimed at effective fractionation of Hermetia illucens into lipid and protein, taking into account the insects’ anatomy. A hybrid approach was developed, separating the exoskeleton by mechanical pressing and fractionating the slurry by sonication and enzymatic treatment. Microscopy showed the peripheral fat bodies were tightly attached to muscle fibers. Blanching caused protein aggregation and entrapment of fat in the protein matrix, resulting in 25.0% loss in fat extraction, compared to only 3.3% loss for unblanched larvae. After centrifugation of the juice obtained from unblanched larvae a cream layer rich of lipids and proteins, a supernatant with soluble protein, and a pellet including mainly insoluble protein were obtained. Blanched juice centrifugation formed a lipid fraction, a reduced cream layer, and more pellet. Whereas sonication hardly affected the fractionation, enzymatic treatment resulted in solubilisation of pellet protein and an increased lipid layer. Absence of blanching is very effective to extract more lipids (>80%) from whole larvae in the form of a cream layer, while blanched-enzymatic treatment extracted most lipids in a clear lipid layer (>40%). For all treatments around 50% of protein was recovered in the residue and the other 50% mainly in the pellet after centrifugation.